2022
DOI: 10.3390/jcm11216456
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Temporal Muscle Thickness in Chronic Subdural Hematoma

Abstract: Background: Reduced temporal muscle thickness (TMT) was verified as an independent negative prognostic parameter for outcome in brain tumor patients. Independent thereof, chronic subdural hematoma (CSDH) is a neurosurgical condition with high recurrence rates and unreliable risk models for poor outcome. Since sarcopenia was associated with poor outcome, we investigated the possible role of TMT and the clinical course of CSDH patients. Methods: This investigation is a single-center retrospective study on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In patients with brain metastases, thicker TMTs (>median) were associated with higher OS in studies of melanoma (146 patients) [ 34 ], and a median-based sex-related TMT cutoff in non-small cell lung cancer (221 patients) was identified as a potential prognostic factor [ 16 ]. TMT has also been investigated as a predictor of clinical outcomes in other pathologies, including primary central nervous system lymphoma (128 patients), head and neck squamous cell carcinoma (106 patients), chronic subdural hematoma (171 patients), and acute ischemic stroke (265 patients) [ 17 , 20 , 21 , 35 ]. However, the results are often contradictory, as, for example, in stroke patients, variations of TMT in terms of OS or mRS after three months show different results in different patient cohorts [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with brain metastases, thicker TMTs (>median) were associated with higher OS in studies of melanoma (146 patients) [ 34 ], and a median-based sex-related TMT cutoff in non-small cell lung cancer (221 patients) was identified as a potential prognostic factor [ 16 ]. TMT has also been investigated as a predictor of clinical outcomes in other pathologies, including primary central nervous system lymphoma (128 patients), head and neck squamous cell carcinoma (106 patients), chronic subdural hematoma (171 patients), and acute ischemic stroke (265 patients) [ 17 , 20 , 21 , 35 ]. However, the results are often contradictory, as, for example, in stroke patients, variations of TMT in terms of OS or mRS after three months show different results in different patient cohorts [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that skeletal muscle mass may be a useful prognostic marker in critically ill patients. The loss of muscle mass, known as sarcopenia, is associated with poor outcomes in various medical and surgical conditions, including brain metastasis, head and neck carcinoma, chronic subdural hemorrhage, intracranial aneurysm, stroke, and glioblastoma [ 16 , 17 , 18 , 19 , 20 , 21 ]. However, clinical diagnosis of sarcopenia, including measuring walking speed or hand strength, can be challenging to implement in aSAH patients with neurological deficits or impaired vigilance [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diminished thickness of the temporal muscle (TMT) has been identified as an adverse prognostic factor in patients with brain tumors [26]. Separately, chronic subdural hematoma (CSDH) is a neurosurgical condition notorious for its high recurrence and elusive outcome prediction models.…”
Section: Applications Of Image Analysis In Musculoskeletal Imagingmentioning
confidence: 99%
“…Several factors, such as age, previous bleeding episodes, cerebral atrophy, alcohol consumption, the presence of subdural air, radiological signs, and surgical techniques, have been identified as potential contributors to recurrence (9)(10)(11). Nevertheless, existing predictive measures have shown inconsistent results and have not seen widespread clinical adoption (12). In recent years, several models predicting the recurrence of CSDH after surgery have been published.…”
Section: Introductionmentioning
confidence: 99%